2010
DOI: 10.1038/oby.2009.176
|View full text |Cite
|
Sign up to set email alerts
|

A Murine Model of Obesity With Accelerated Atherosclerosis

Abstract: The epidemic of obesity sweeping developed nations is accompanied by an increase in atherosclerotic cardiovascular diseases. Dyslipidemia, diabetes, hypertension, and obesity are risk factors for cardiovascular disease. However, delineating the mechanism of obesity‐accelerated atherosclerosis has been hampered by a paucity of animal models. Similar to humans, apolipoprotein E–deficient (apoE−/−) mice spontaneously develop atherosclerosis over their lifetime. To determine whether apoE−/− mice would develop obes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
66
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 37 publications
6
66
0
Order By: Relevance
“…These changes in microbiota increased the capability to break down fiber into short chain fatty acids and to release additional energy, which could be converted into fat 28) . ApoE-deficient mice fed a high fat diet were recently found to exhibit a chronic level of inflammation, which may mediate the formation of atherosclerotic lesions 29) . The influence of probiotic bacteria was studied in patients with a high cholesterol level supplemented with L. plantarum 299v.…”
Section: Discussionmentioning
confidence: 99%
“…These changes in microbiota increased the capability to break down fiber into short chain fatty acids and to release additional energy, which could be converted into fat 28) . ApoE-deficient mice fed a high fat diet were recently found to exhibit a chronic level of inflammation, which may mediate the formation of atherosclerotic lesions 29) . The influence of probiotic bacteria was studied in patients with a high cholesterol level supplemented with L. plantarum 299v.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we found that apoE -/-mice fed a high-fat diet (with 60% of the calories from fat) for 17 weeks have increased body weight and atherosclerosis (King et al, 2009). These high-fatfed apoE -/-mice are glucose intolerant and also display elevated systemic inflammation, as measured by increased serum amyloid A concentrations in the plasma.…”
Section: Apolipoprotein E (Apoe)-deficient Micementioning
confidence: 99%
“…The serum adiponectin concentration after 12 weeks of HF + PP feeding did not change significantly when compared with HF feeding. There was a report that ApoE-deficient mice fed high fat diet had a marked atherosclerotic lesion formation, but did not show significant difference in adipocytokine levels including adiponectin [40].…”
Section: Discussionmentioning
confidence: 99%